SOLID DISPERSION OF NEBIVOLOL HYDROCHLORIDE IMPREGNATED BUCCAL PATCH: FORMULATION AND CHARACTERIZATION - JOSE, CLINTON; PRIYA, SNEH; JYOTHI, DIVYA; JOSHI, HIMANSHU; LOBO, CYNTHIA LIZZIE; S. P., KRITHI (International Journal of Applied Pharmaceutics, 2021)
Objective: The objective of the present investigation was to design and characterize a mucoadhesive buccal patch of Nebivolol hydrochloride in order to administer a small dose of a drug to treat hypertension effectively and thereby avoiding disadvantages such as patient noncompliance and low bioavailability. Methods: The buccal patches were prepared by solvent casting method. The polymers used to formulate patches were HPMC K 15 M, PVP K 30, and propylene glycol was used as plasticizer and ethanol as the solvent. The drug-polymer compatibility studied was conducted by FTIR. Results: All the developed Patches had good transparency and stability. All formulated patches showed pH in the range of 6.49 to 7.22, and drug content was more than 90%. The folding endurance value showed that the patches are flexible and non-brittle. The in vitro residence time was found to more than 30 min. Thickness, % moisture absorption, and % moisture loss values were in a normal range. The drug release study was conducted for 8 h, and it was found drug release was decreased with the increase in polymer concentration. The in vitro release profiles of the drug from all the formulations appeared to follow Korsmeyer Peppa's exponential model, and release exponent (n) was found to be more than 0.45 so that the release can be characterized by Non–Fickian (anomalous) diffusion. Conclusion: From the results, it was concluded that drug released from formulated buccal patches follows sustained release pattern, Hence can be used for the treatment of the hypertensive patient.